2002
DOI: 10.1210/jc.2002-020505
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Ghrelin Levels in Patients with Polycystic Ovary Syndrome

Abstract: The syndrome of polycystic ovaries (PCOS) is associated with adiposity and metabolic changes predisposing to insulin resistance and diabetes mellitus. Because the recently discovered GH secretagogue, ghrelin, is intimately involved in the control of appetite and weight regulation, we studied ghrelin levels in a group of 26 otherwise healthy women with PCOS. They were compared with 61 healthy female control subjects and 5 gastrectomized women. Insulin sensitivity was assessed by homeostasis model assessment (HO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
91
4
9

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(114 citation statements)
references
References 28 publications
10
91
4
9
Order By: Relevance
“…Low ghrelin concentrations were shown to associate independently with Type 2 diabetes and insulin resistance (Pöykkö et al, 2003). A strong inverse correlation between ghrelin concentrations and insulin resistance measured by homeostasis model of insulin resistance (HOMA-IR) and/or insulin concentrations has been observed also in other studies, for example among women with polycystic ovary syndrome (Schöfl et al, 2002) and in obese middle-aged subjects (McLaughlin et al, 2004). A recent study that aimed to clarify the relationships between total, acylated and des-acylated ghrelin molecules specifically with insulin resistance showed that these molecules might be involved in glucose and insulin metabolism in different ways.…”
Section: Ghrelin In Type 2 Diabetes Mellitussupporting
confidence: 65%
See 1 more Smart Citation
“…Low ghrelin concentrations were shown to associate independently with Type 2 diabetes and insulin resistance (Pöykkö et al, 2003). A strong inverse correlation between ghrelin concentrations and insulin resistance measured by homeostasis model of insulin resistance (HOMA-IR) and/or insulin concentrations has been observed also in other studies, for example among women with polycystic ovary syndrome (Schöfl et al, 2002) and in obese middle-aged subjects (McLaughlin et al, 2004). A recent study that aimed to clarify the relationships between total, acylated and des-acylated ghrelin molecules specifically with insulin resistance showed that these molecules might be involved in glucose and insulin metabolism in different ways.…”
Section: Ghrelin In Type 2 Diabetes Mellitussupporting
confidence: 65%
“…One such molecule is ghrelin, a blood-borne orexigenic signal from gut to brain (Kojima et al, 1999), with multiple hormonal, metabolic, and cardiovascular activities (Kojima et al, 2005). Low ghrelin concentrations have been associated with the components of the MS, like obesity (Tschöp et Page 3 of 13 A c c e p t e d M a n u s c r i p t 3 al., 2001), insulin resistance (Bacha and Arslanian, 2005;Pöykkö et al, 2003;Schöfl et al, 2002), and blood pressure (Fagerberg et al, 2003;Pöykkö et al, 2003). The negative association between ghrelin and waist circumference, a prerequisite for the MS, has also been reported (Fagerberg et al, 2003).…”
Section: Ghrelin In Metabolic Syndromementioning
confidence: 99%
“…There have been few studies of ghrelin in PCOS, and most have focused on fasting (total) ghrelin levels (9)(10)(11)(12)(13). These have yielded inconsistent and conflicting data to support both normal (14) and abnormal (significantly lower) fasting serum ghrelin levels in women with PCOS versus controls (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…These have yielded inconsistent and conflicting data to support both normal (14) and abnormal (significantly lower) fasting serum ghrelin levels in women with PCOS versus controls (9)(10)(11). In a couple of studies, a significant negative correlation between fasting serum ghrelin and homeostasis model assessment of insulin resistance (HOMA2 IR; a measure of insulin sensitivity) has been demonstrated (9,11). However, only one previous study has assessed postprandial serum ghrelin levels in PCOS (15), and the lack of equivalent postprandial data in other studies represents a significant limitation of the current literature.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that ghrelin levels in obese PCOS were lower than in weightmatched control subjects without PCOS, and an inverse correlation between androgen (particularly androstenedione) blood levels has been found (Barber et al, 2008;Bideci et al, 2008;Glintborg et al, 2006;Moran et al, 2004;Pagotto et al 2002;Panidis et al, 2005;Panidis et al, 2010;Sağsöz et al, 2009;Schöfl et al, 2002;Zwirska-Korczala et al, 2008), although some studies could not confirm these findings (Orio et al, 2003;Wasko et al, 2004). In one study, an inverse correlation has been reported between the hirsutism score and ghrelin concentrations (Panidis et al, 2010).…”
Section: Ghrelin and The Polycystic Ovary Syndromementioning
confidence: 99%